Roman lead-glazed pottery trade from Italy to southern Gaul and its influence on local production: The example of the Capitou workshop (France) - Gohier, Pauline (Rei Cretariae Romanae Fautorum Acta, 2022)
The Capitou workshop in Servian (Hérault, France) is one of the few workshops in southern Gaul to attempt to produce lead-glazed ceramics during the 2nd century AD. This period is marked by regular imports of lead-glazed ceramics from Italian workshops in the Lazio region, and especially from Rome. Recent studies have highlighted the existence of real trade, although on a small scale, from Italy to Gaul. Various forms of lead-glazed pottery from central Italy are found on several consumption sites. The lead-glazed ceramics from Capitou and the Italian workshops show great technological, typological and decorative similarities. This is particularly the case for products of the Janiculum workshop in Rome. The technique of lead-glazing seems to have been imported directly from Italian workshops. These new data highlight the principal questions about trade in lead-glazed ceramics during the High Empire and about the transfer of the glazing technology.